Experience in the use of MOSES technology for endoscopic treatment of benign prostatic hyperplasia - K. S. Peshekhonov; O. O. Burlaka; E. S. Shpilenia; B. K. Komyakov (Вестник урологии, 2020)
Introduction. The development of laser technologies in medicine and their introduction into everyday clinical practice determine the trend of using this type of energy in the treatment of patients with lower urinary tract symptoms caused by benign prostatic hyperplasia (BPH). In the last decade, holmium laser enucleation (HoLEP) of the prostate has been claiming to be «the gold standard» in the BPH treatment. The advantages of HoLEP over alternative technologies (transurethral resection, bipolar enucleation) in the BPH treatment have been demonstrated in randomized trials. These advantages include the reduction of the patient's hospital stay, safety of manipulation and high quality of life for the patient after surgery. The use of electrical energy in resection techniques for the BPH treatment in most cases is limited by the prostate volume (80 cm3). A better understanding of the effect of laser radiation and its clinical efficacy has led to increased interest and widespread adoption of laser systems. The constant search and improvement of existing approaches encourages urologists and surgical equipment companies to research new laser systems. One type of improvement is a software update for laser pulse modulation that has been developed to improve the efficiency of laser equipment. For the further development of new laser technologies and widespread use in routine clinical practice, it is necessary to compare them with standard methods of BPH surgical treatment with an assessment of the effectiveness, as well as the pros and cons of the compared methods.Purpose of the study. To evaluate the results of laser endoscopic treatment of patients with prostatic hyperplasia.Materials and methods. The study included 50 patients with prostatic hyperplasia who underwent two different types of surgery — HoLEP (group I; n = 25) and HoLEP with MOSES (HoLEP-M) technology (group II; n = 25). Inclusion criteria were: the presence of moderate or severe obstructive symptoms of the lower urinary tract, prostate volume > 40 cm3, maximum urine flow (Q-max) < 12 ml/sec. Exclusion criteria were: the presence of cystostomy drainage, an oncological process of the urinary system, an active inflammatory process of the genitourinary system, previous surgical interventions on the urinary system. I-PSS, QoL and IIEF questionnaires data, the level of prostate-specific antigen (PSA), the maximum flow of the urine stream (Q-max) and the post-void residual volume were assessed at baseline and 3 months after the operation. The main indicators of the compared methods, the number and nature of complications were studied.Results. Both methods of laser enucleation allow achieving a good functional result with a minimum number of complications. When comparing both methods in the group II of patients who underwent HoLEP-M, there was a statistically significant difference in terms of characteristics: the time of enucleation in group I (HoLEP) — 46.7 ± 15.0 min (31 - 80) vs group II (HoLEP-M) — 38.9 ± 7.6 min (30 - 60) (p = 0.03), but this did not affect the total time of surgery (p = 0.21), the level of haemoglobin postoperative changes in group I (HoLEP) — 7.5 ± 5.4 g/l (2 - 18) vs group II (HoLEP-M) — 5.0 ± 2.9 g/l (2 - 13) (p = 0.04) and irrigation time in the postoperative period, group I (HoLEP) — 17.6 ± 3.6 h (11 - 26) vs group II — 14.0 ± 4.3 h (5 - 21) (p < 0.001). Thus, the results of the study suggest that the HoLEP with the modified pulse MOSES technology has advantages over the standard HoLEP technique. HoLEP-M allows you to perform the enucleation stage faster, with better hemostasis and minimizes the effect of the laser on the surrounding tissues. Complications above level 2 were not observed in both groups according to the Clavien-Dindo scale.Conclusion. HOLEP-M is a safe method of surgical treatment of prostatic hyperplasia from the point of view of surgical safety, efficacy, as well as the duration of the patient's recovery period and can serve as an alternative to the HoLEP standard technique.